Phylogeny of the genus Fuscoporia and taxonomic assessment of the F. contigua group. (4th May 2019) - Chen, Qian; Wu, Fang; Ji, Xiao-Hong; Si, Jing; Zhou, Li-Wei; Tian, Xue-Mei; Vlasák, Josef; Dai, Yu-Cheng
ABSTRACT: The genus Fuscoporia of the Hymenochaetaceae is characterized by resupinate to pileate basidiocarps, a dimitic hyphal system with fine crystal aggregates and encrusted generative hyphae in dissepiment edge and tube trama, the presence of hymenial setae, and hyaline, thin-walled, smooth basidiospores. Members of the F. contigua group are easy to distinguish from other species of Fuscoporia because of the moderately large pores, presence of mycelial setae, and large hymenial setae. Here, we explore phylogenetic relationships among 20 species of Fuscoporia based on examination of some 90 collections sampled worldwide. Seven new species are recognized in the F. contigua group— F. americana, F. centroamericana, F. costaricana, F. latispora, F. monticola, F. septiseta, and F. sinica —described from China, Costa Rica, Mexico, and the United States. Phylogenetic analyses inferred from DNA sequences of the nuc rDNA internal transcribed spacer (ITS1-5.8S-ITS2 = ITS), D1–D2 domains of nuc 28S rDNA (28S), and translation elongation factor EF-1 alpha ( tef1 ) support the F. contigua group as one of two major clades within Fuscoporia comprising nine species worldwide.